Emergency clinic dermatology and primary care. Issue 9 (September 2020) - Jmor, Shilan; Rutkowski, David; Cummins, Donna; McMullen, Emma
GPs conduct approximately 13 000 000 consultations relating to skin conditions on an annual basis. The majority of chronic skin disease can be supervised in the primary care setting, however, high rates of morbidity and mortality are associated with a proportion of presentations, for which early diagnosis and prompt referral to a specialist dermatology service is required. Despite this, dermatology remains a relatively low priority in undergraduate and postgraduate medical training, leaving many GP trainees with limited exposure. We will highlight key clinical signs and construct a basic algorithm to help trainees structure their approach when managing these patients.